Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Lingkungan Kerja terhadap Motivasi Kerja Guru di Mts Negeri 1 Jombang - Badi’atun Nadhiroh; Suwandi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Teacher work motivation can be interpreted as internal and external encouragement that encourages a teacher to carry out his duties and responsibilities with enthusiasm, dedication and effectiveness. Motivation can also support the role of a teacher and have a positive impact on the quality of teaching and student learning outcomes. This research has the objectives, (1) To find out whether there is an influence of the principal's leadership style on teacher work motivation at MTs Negeri 1 Jombang. (2) To find out whether there is an influence of the work environment on teacher work motivation at MTs Negeri 1 Jombang. (3) To find out whether there is a simultaneous influence of the principal's leadership style and work environment on teacher work motivation at MTs Negeri 1 Jombang. This research uses a quantitative approach with an ex post facto type of research. The sample in this research was 57 teachers as respondents, using probability sampling using a saturated sampling technique. Data collection was carried out using a questionnaire distribution in the form of 36 (thirty six) question items. And using data analysis techniques with multiple linear regression tests. The results of this research show that, (1) The principal's leadership style using the calculated T test with a significance value of 0.000 < 0.05 and a calculated T result of 14,238 (14,238 > 2.006) means that Ho is rejected and Ha is accepted. This means that the principal's leadership style variable (X1) has a significant influence on the teacher's work motivation variable (Y). (2) Work environment using the calculated T test with a significance value of 0.000 < 0.05 and a calculated T result of 4.610 (4.610 > 2.006), then Ho is rejected and Ha is accepted. This means that the work environment variable (X2) has a significant influence on teacher work motivation (Y). (3) The principal's leadership style and work environment on teacher work motivation using the calculated F test with a significance value of 0.000 < 0.005 and the calculated F result is 20.284 (20.284 > 2.7758), so Ho is rejected and Ha is accepted.